EFEKTIFITAS ICE CREAM TERHADAP PENURUNAN EMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER 1 DI PUSKESMAS JAMBESARI BONDOWOSO - Sulalah, Anis; Natalia, Mega Silvian; Ekasari, Tutik (NHM PRESS, 2024)
Emesis Gravidarum is a disorder that we often encounter in young pregnancies and is proposed by 50% of women. The purpose of the study was to analyze the effectiveness of ice cream on reducing emesis gravidarum in 1st trimester pregnant women at Jambesari Bondowoso Health Center. This research design is an experimental research with one group pre test-post test design. The population in this study was 59 first trimester pregnant women. The sample size in this study was 37 people taken by random sampling. Data collection using questionnaires was then processed using SPSS using the Wilcoxon test. The results of data analysis found that most Emesis Gravidum before ice cream therapy was moderate as many as 28 people (71.8%), and most Emesis Gravidum after ice cream therapy was mild as many as 20 people (51.3%). Based on the Wilcoxon test, a significance value of 0.000 < 0.05 was obtained, meaning that ho was rejected and ha was accepted, so there was a difference in ice cream therapy against Emesis Gravidum at the Jambesari Bondowoso Health Center. It is recommended that respondents when nauseous to consume ice cream.